Encontrando um novo Mefisto : a americanização do exército brasileiro e a revista A defesa nacional, 1942-1950 - Stumpf, Derli Junior (2010)
The present work presents results of a research that investigates the North American military influence in the Brazilian Army throughout the period of direct involvement of the Unites States of America in the World War II, as well in the initial context of Cold War. It is checked, here, from the military press, more specifically through the analysis of the articles published in the magazine A Defesa Nacional (The National Defense) from 1942 to 1950, how the transition from French military headquarters to another North American in the Brazilian Army happened. Concerning the theoretical methodological aspects, the research uses the conceptual apparatus of the Cultural History, more specifically in the concept of representations, elaborated by the historian Roger Chartier. This way, the work concludes that the incorporation of the American military model, according to the published on the pages of the magazine, by the Brazilian army, happened in a selective and pragmatic way, even in periods when the national external politics aligned automatically with the North American diplomacy. Finally, there was not an automatic assimilation of the North American model by the Brazilian army, that put the interests of the institution above any eventual sympathy and unrestricted support to the demand of the American military